The volatile emission of a specialist herbivore alters patterns of plant defence, growth and flower production in a field population of goldenrod. (2nd March 2017) - Yip, Eric C.; De Moraes, Consuelo M.; Mescher, Mark C.; Tooker, John F.
Summary: Plants frequently employ induced, rather than constitutive, defences against herbivores and pathogens, presumably as an adaptive response to the unpredictability of attack by particular antagonists. Plants may further accelerate defence deployment by 'priming' appropriate defences in response to environmental cues that reliably predict impending attack. However, the population‐ and community‐level ecological consequences of such priming remain relatively unexplored. We recently discovered that the volatile emissions of male Eurosta solidaginis prime the antiherbivore defences of its host plant, tall goldenrod ( Solidago altissima ). This co‐evolved system provides a unique opportunity to study the ecological consequences of priming in a natural system. We explored effects of the priming cue on neighbouring ramets at varying distances from the emission source by quantifying subsequent levels of foliar herbivory, as well as plant growth and flower production (which might reveal trade‐offs between investment in growth or reproduction and defence). We observed a linear increase in leaf damage with distance from the emission source (up to our maximal distance of 1 m), consistent with the hypothesis that the intensity of priming corresponds to the intensity of exposure to the fly emission. Unexpectedly, ramets nearest the emission source also exhibited a short‐term increase in growth‐rate; however, this effect did not persist to the end of the season or increase flower production. Instead, ramet's mid‐distance from the emission source exhibited reduced growth and flower production compared to those nearer or farther away. Synthesis . The responsiveness of Solidago altissima ramets to herbivore‐associated cues across a distance of 1 m or more is highly relevant in this system, where individual ramets frequently grow within a few cm of one another. Furthermore, the resulting mosaic of ramets primed to varying degrees might influence herbivore (and consequently predator) distributions. The unexpected decline in flower production by mid‐distance ramets suggests that the effects of plant priming on ecological interactions among plants and other organisms (such as tritrophic interactions and competition) may feed back onto plant fitness in complex, and as yet unexplored, ways. A lay summary is available for this article. Abstract : Lay Summary